Distribution and Characterisation of Tick-Borne Flavi-, Flavi-like, and Phenuiviruses in the Chelyabinsk Region of Russia - Kholodilov, Ivan; Belova, Oxana; Ivannikova, Anna; Gadzhikurbanov, Magomed; Makenov, Marat; Yakovlev, Alexander; Polienko, Alexandra; Dereventsova, Alena; Litov, Alexander; Gmyl, Larissa; Okhezin, Egor; Luchinina, Svetlana; et al. (Viruses, 2022)
In this work, we presented data from a two-year study of flavi-, flavi-like, and phenuiviruses circulation in the population of ixodid ticks in the Chelyabinsk region. We isolated three tick-borne encephalitis virus (TBEV) strains from I. persulcatus, which was not detected in the ticks of the genus Dermacentor. The virus prevalence ranged from 0.66% to 2.28%. The Yanggou tick virus (YGTV) is widespread in steppe and forest-steppe zones and is mainly associated with ticks of the genus Dermacentor. We isolated 26 strains from D. reticulatus, D. marginatus, and I. persulcatus ticks in the HAE/CTVM8 tick cell line. The virus prevalence ranged from 1.58% to 4.18% in D. reticulatus, ranged from 0.78% to 3.93% in D. marginatus, and was 0.66% in I. persulcatus. There was combined focus of TBEV and YGTV in the territory of the Chelyabinsk region. The Alongshan virus (ALSV) was found to be associated with I. persulcatus ticks and is spread in forest zone. We detected 12 amplicons and isolated 7 strains of ALSV in tick cells. The virus prevalence ranged from 1.13% to 6.00%. The phlebovirus Gomselga and unclassified phenuivirus Stavropol were associated with I. persulcatus and D. reticulatus ticks, respectively. Virus prevalence of the unclassified phenuivirus Stavropol in the Chelyabinsk region is lower than that in neighbouring regions.